Energy systems integration as research practice. Issue 3 (4th March 2023) - Silvast, Antti; Abram, Simone; Copeland, Claire
ABSTRACT: This article adopts frameworks and methods from Science and Technology Studies for examining Energy Systems Integration (ESI). ESI, the integrated operation and planning of multiple energy supplies and demands, can contribute to improvements in energy reliability, security and flexibility, and therefore facilitate a transition to a low carbon economy. The article examines UK research towards integrated computer models of energy system 'vectors'. The research is based on fieldwork and participation in a large ESI research project in the UK, drawing on interviews, workshops and observations. We highlight three main contributions to the studies on ESI and STS research of modelling. First, ESI researchers are aware of the social, economic and political context of their work, though many of these contexts are difficult to incorporate in any useful modelling process. Second, issues that touch on both science and policy around energy systems were the motivation for ESI researchers yet were also underemphasised in project work. Third, we develop unique mixed ethnographic methods to study ESI and that enable researchers to build relations of trust with research participants that contribute to the discussion of sensitive topics such as the politics and ethics of energy modelling approaches.